2015
DOI: 10.1098/rsbl.2015.0800
|View full text |Cite
|
Sign up to set email alerts
|

Electric shock causes physiological stress responses in shore crabs, consistent with prediction of pain

Abstract: Animal pain is defined by a series of expectations or criteria, one of which is that there should be a physiological stress response associated with noxious stimuli. While crustacean stress responses have been demonstrated they are typically preceded by escape behaviour and thus the physiological change might be attributed to the behaviour rather than a pain experience. We found higher levels of stress as measured by lactate in shore crabs exposed to brief electric shock than non-shocked controls. However, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 21 publications
2
41
0
1
Order By: Relevance
“…Without an understanding of the neural architecture or minimum brain size required to support subjective experience, we are left with no neurobiological method of determining whether insects experience pain (also see Elwood, 2011). Merely pointing out that insect brains have a different neuroanatomical structure than mammals does not demonstrate that they are incapable of experiencing an emotional response to pain; insects could use different neurobiological mechanisms (Sherwin, 2001).…”
Section: Evidence From Insect Neurobiologymentioning
confidence: 98%
“…Without an understanding of the neural architecture or minimum brain size required to support subjective experience, we are left with no neurobiological method of determining whether insects experience pain (also see Elwood, 2011). Merely pointing out that insect brains have a different neuroanatomical structure than mammals does not demonstrate that they are incapable of experiencing an emotional response to pain; insects could use different neurobiological mechanisms (Sherwin, 2001).…”
Section: Evidence From Insect Neurobiologymentioning
confidence: 98%
“…Other scientists have suggested however, that the presence of a centralised nervous system that is protected by a blood-brain interface, and particularly, the rather complex behavioural reactions in octopuses and in mollusc cephalopods in general to various situations, including injury, would suggest at least the possibility of the presence of some degree of a negative affective experience in response to a nociceptive stimulation (Barr et al, 2008). Similarly, the behaviours of crustaceans present a certain complexity and some scientists interpret their reactions to nociceptive stimuli as indicative of at least some degree of a negative affective experience associated with nociception (Magee and Elwood, 2013;Elwood and Adams, 2015).…”
Section: Nociception and Potential Pain In Invertebratesmentioning
confidence: 99%
“…The shocked crabs nevertheless had greater physiological signs of stress than did controls. The paper [2] considered if that might be due to greater muscular activity but concluded that there were no overt signs of such activity. The critique suggests that heart and 'breathing' rates should have been monitored.…”
mentioning
confidence: 99%
“…The paper [2] provides a way of largely overcoming this problem by comparing subgroups of shocked and non-shocked crabs that showed a similar level of behaviour. The shocked crabs nevertheless had greater physiological signs of stress than did controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation